Multiple objectives hybrid metaheuristic for spatial-based redistricting : the framework and algorithms - Bong, Chin Wei (Faculty of Computer Science and Information Technology, 2006)
This research has designed and developed a generic multiple objectives decision support framework for redistricting to provide a more realistic perception of redistricting problems. This thesis considers the multiple objective definition, identifies a wider range of alternatives, and describes the relationship between alternatives.